An intelligent method for optimization of tariffs in GSM networks - Kaya, Buket (Institute of Electrical and Electronics Engineers Inc., 2016)
GSM is a mobile technology that allows people to communicate with one another. The technology enables people to call others over the phone with a GSM number and a certain tariff for communication. An interpersonal GSM network is established by means of calls and text messages. This paper proposes an approach to recommend optimal tariffs to GSM users to maximize the total utility of individuals in the GSM network. However, finding optimal tariffs for very large GSM networks is computationally intractable by standard methods. For this purpose, we present a novel multi-agent based algorithm to recommend the most appropriate tariffs to a specific group of GSM users. The results of the experiment on a synthetic GSM network comprised of users with various tariffs suggest that the method is practical and able to yield accurate results. © 2016 IEEE.
2016 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining, ASONAM 2016 -- 18 August 2016 through 21 August 2016 -- San Francisco -- 125031
Keywords: GSM tariffs; Recommendation systems; Social networks